The role of primary care in adult weight management: qualitative interviews with key stakeholders in weight management services - David N. Blane; Sara Macdonald; David Morrison; Catherine A. O'Donnell (BMC, 2017)
Abstract Background Primary care has a key role to play in the prevention and management of obesity, but there remain barriers to engagement in weight management by primary care practitioners. The aim of this study was to explore the views of key stakeholders in adult weight management services on the role of primary care in adult weight management. Methods Qualitative study involving semi-structured interviews with nine senior dietitians involved in NHS weight management from seven Scottish health boards. Transcripts were analysed using an inductive thematic approach. Results A range of tensions were apparent within three key themes: weight management service issues, the role of primary care, and communication with primary care. For weight management services, these tensions were around funding, the management model of obesity, and how to configure access to services. For primary care, they were around what primary care should be doing, who should be doing it, and where this activity should fit within wider weight management policy. With regard to communication between weight management services and primary care, there were tensions related to the approach taken (locally adapted versus centralised), the message being communicated (weight loss versus wellbeing), and the response from practitioners (engagement versus resistance). Conclusions Primary care can do more to support adult weight management, but this requires better engagement and communication with weight management services, to overcome the tensions highlighted in this study. This, in turn, requires more secure, sustained funding. The example of smoking cessation in the UK, where there is a network of well-resourced NHS Stop Smoking Services, accessible via different means, could be a model to follow.